以文化－本位課程模式建構原住民族教育之探究 Constructing Indigenous Education Based on Culture-Based Curriculum - 洪清一 Ching-I Horng; 陳秋惠 (通訊作者) (Higher Education Foundation, 2014)
原住民文化具有獨特性、殊異性和多元性，但卻容易因主流文化，而有著丟失其傳統珍貴文化的風險。文化－本位課程（culture-based curriculum）旨在強調原住民文化之主體性、生活化、多樣性、功能性或實用性之理念，以原住民為主體，經由原住民與其傳統的對話，以及原住民主體社會的對話建構原住民族教育。在文化－本位課程模式建構下，整理出原住民族教育之文化－本位課程包括族語暨文學、傳統生活技能、社會組織、藝術與樂舞、傳統信仰與祭儀、族群關係與部落歷史、部落倫理與禁忌、環境生態保育等領域，且在領域下細分不同項目。本研究綜述多篇文獻，整理出文化－本位課程之發展順序及評量建議，期望激發更富有意義性的教學方案設計。Indigenous culture is unique, distinct and diverse. However, the indigenous people are now under a risk of losing their precious traditional culture because of the dominant non-indigenous culture. Culture-based curriculum is designed to emphasize the concept of subjectivity, life, diversity, functionalist or practicality in indigenous culture. Culture based curriculum is the indigenous education constructed through the interaction between indigenous people and their tradition and society. Base on the construction of the culture - based curriculum model, it is categorized into nine fields including ethnic language and literature, skills of traditional lives, social organization, art and dance, traditional beliefs and rituals, ethnic relations and tribal history, tribal ethics and taboos, and environmental and ecological conservation, and under each fields are more specific subcategories. According reviewing the related papers, the current study suggests the order of development and the recommendations of assessment for culture-based curriculum to shed light on more meaningful programs of teaching design.